KEMAMPUAN MENULIS TEKS BERITA PADA PESERTA DIDIK KELAS VIII MTs DDI BASSEANG - Suhaebah Nur (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2014)
This study aimed to describe the ability of learners to write a text message in learning Indonesian language and literature in the eighth grade students of MTs DDI Basseang, District Anreapi Polewali Mandar. Learner performance data and observations were analyzed using qualitative methods. Results of test instrument was analyzed by using the formula percentage that can be seen from the aspect of completeness of the content of news learners categorized as very capable, aspects exposure of most learners categorized as incapable, from the aspects of the use of the phrase most learners categorized as incapable, aspects of the vocabulary used learners categorized less able, the attractiveness of the title of most aspects of learners categorized as incapable, and from the aspect of the use of EYD categorized learners can not afford. While the results of observation and documentation shows only a few students who actually receive lessons, most students do not pay attention or listen to the teacher's explanation, only a few students were enthusiastic in asking questions about the theory of learning.